(untitled) (Comparatismi, 2022)
Complex post-traumatic stress disorder develops following exposure to a series of threatening, prolonged or repetitive events from which it is difficult or impossible to escape. This study aims to investigate how cinema and TV series represent the inhibition to tell one’s story as an effect of this trauma.